Comparative evaluation of diffused calcium and hydroxyl ion release from three different Indirect pulp capping agents in permanent teeth – An in vitro study - M.S. Fahanna Beegum; Sageena George; S. Anandaraj; Jyoti Sumi Issac; S. Nubesh Khan; Mohammed Ali Habibullah (Saudi Dental Journal)
Background: Indirect pulp capping therapy has gained increased popularity in paediatric dentistry since it is less invasive, and is of low cost. The aim of the present study was to evaluate and to compare the diffusion of calcium (Ca2+) and hydroxyl (OH–) ions through coronal dentin into pulp after indirect pulp capping in vitro using TheraCal LC, ProRoot MTA and Calcimol LC. Materials and methods: Total of 60 human caries-free maxillary first premolars were selected for the study. Samples were divided into 4 groups with 15 in each group: Group 1 TheraCal LC; Group 2 ProRoot MTA; Group 3 Calcimol LC; Group 4 Control Group. Indirect pulpcapping on the coronal RDT (remaining dentine thickness) system was performed using pulp-capping materials, such as TheraCal LC, ProRoot MTA and Calcimol LC, on the respective samples. The control group was completely filled with composite. Ca2+ ions (ppm) and OH– ions (pH) were analysed in deionized water using a multimeter connected to a calcium probe (calcium ion electrode) and pH metre connected to a temperature-compensated pH probe after 3 h, 24 h, 7 days, 14 days, 28 days and 60 days. Results: Calcium release was significantly higher (P < 0.05) in the TheraCal LC group than in the other groups. Slightly alkaline pH values were observed in all the groups except for the control. Conclusion: TheraCal is a new light-curable pulp capping material that initially releases high Ca2+ ions and creates an environmental pH close to physiological pH after 60 days.